Determination of factors ınhibiting the physıcal activity status of nursing students in the covid-19 pandemic - Bülbül, Tuba; Tosun, Betül; Di̇Rgar, Ezgi (Nevzat Demirci)
The COVID-19 pandemic, which is accepted as a pandemic by the World Health Organization, has seriously affected life in our country as well as all over the world. Quarantine decisions taken to control the spread of the pandemic caused physical inactivity in people. Especially in the student years, if no direction or intervention is made for insufficient physical activity, it can have negative effects on the health of individuals in the following years. The study, which was designed in descriptive type, was conducted with 261 volunteer students between February and March 2021 in order to determine the factors that prevent the physical activity status of nursing students during the pandemic period. The data were collected online with a questionnaire in which the demographic information and physical activity levels of the participants were questioned, and the 'Physical Activity Barriers Scale' (PABS). Data were given together as number, percentage, median, mean standard deviation, and p[removed]
Keywords: Covid-19; Nursing Students; Pandemic; Physical İnactivity